Hubungan Self Awareness dan Safety Climate Terhadap Safety Behavior pada Karyawan Bengkel Mobil di PT. X - Raka Tegar Pradewa; Iranita Hervi Mahardayani (Universitas Muria Kudus, 2023)
This study determines the relationship between self awareness and safety climate on safety behavior among workshop employees at PT. X. The subjects were PT.X workshop employees in all branches in the Semarang area, who worked for more than 3 years, used high-risk tools, and had technician certificates. The sampling used purposive sampling, with a total of 94 people who met the criteria. The scale is summated rating scale, safety behavior scale, self awareness scale, and safety climate scale. The correlation coefficient of the three variables rx1,2y is 0.766 (p 0.01) so there is a significant relationship between self awareness (X1) and safety climate (X2) with safety behavior (Y) with an effective contribution of 58.7% .So the major hypothesis there is a relationship between self awareness (X1) and safety climate (X2) on safety behavior (Y) is accepted. The results of the analysis of the variable self awareness (X1) with safety behavior (Y) show rx1y of 0.708 (p 0.01) and an effective contribution of 50.1%. So, there is a positive relationship between self awareness and safety behavior, the first hypothesis is accepted. While the results of the analysis of the variable safety climate with safety behavior show rx2y of 0.687 (p 0.01) with an effective contribution of 47.2%. So, there is a positive relationship between safety climate and safety behavior, and the second hypothesis is accepted. Penelitian ini bertujuan untuk mengetahui hubungan antara self awareness dan safety climate terhadap safety behavior pada karyawan bengkel di PT. X. Subyek penelitian adalah karyawan bengkel PT.X seluruh cabang area Semarang, yang bekerja lebih dari 3 tahun, menggunakan alat berisiko tinggi, dan memiliki sertifikat teknisi. Teknik pengambilan sampel menggunakan Purposive Sampling, total yang memenuhi kriteria sebanyak 94 orang. Skala yang digunakan yaitu skala summated rating, skala safety behavior, skala self awareness dan skala safety climate. Koefisien korelasi ketiga variabel rx1,2y sebesar 0,766 (p 0,01) maka ada hubungan yang sangat signifikan antara self awareness (X1) dan safety climate (X2) dengan safety behavior (Y) dengan sumbangan efektif 58,7%. Maka hipotesis mayor dalam penelitian ini yaitu ada hubungan antara self awareness (X1) dan safety climate (X2) terhadap safety behavior (Y) diterima. Hasil analisis variabel self awareness (X1) dengan safety behavior (Y) menunjukan rx1y sebesar 0,708 (p 0,01) dan sumbangan efektif 50,1%. Maka ada hubungan positif antara self awareness dengan safety behavior, hipotesis pertama diterima. Sedangkan hasil analisis variabel safety climate dengan safety behavior menunjukan rx2y sebesar 0,687 (p 0,01) dengan sumbangan efektif 47,2%. Maka ada hubungan positif antara safety climate dengan safety behavior, hipotesis kedua diterima.